Which Culture(s) for Europe? The Contrasting Conceptions of the Council of Europe and the European Union from 1949 to the Present Day - Calligaro, Oriane (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
Two European organizations of a very different nature have taken action to promote and support European culture: the Council of Europe and the European Union. This article aims to show that, despite common symbolic references and mutual influences, the two organizations’ conceptions of culture do not coincide. A socio-historical and comparative analysis of the emergence and evolution of their respective cultural programmes allows us to reconstruct on the long term their visions and usages of culture. Both organizations initially resorted to European culture in a celebratory and legitimizing manner but their approach soon became distinct. The European Commission has durably proposed top-down, elite-driven and static narratives of European culture, which repeatedly drew criticism, also from other actors within the EU institutions. The CoE, on the contrary, has very soon conceptualized culture as open, decentralized and with porous boundaries. These divergent visions will also be observed in the two organizations’ interactions in the cultural domain, which oscillate between competition and collaboration. In contemporary academic debates, the question of the historical and cultural boundaries of Europe are often explored in close connection to the EU’s political agenda and institutional frame. As a contribution to the “provincializing” of the EU, a socio-historical approach including an understudied European organization, the Council of Europe, makes it possible to critically reassess the understanding and usage of culture in the context of European integration.